Revision of 1895: The General Ordinances of the City of Indianapolis 290-291 (1895) - (:unkn) unknown (My University, 1895)
Be it ordained by the Common Council and Board of Aldermen of the City of Indianapolis, That it shall hereafter be unlawful for any person to conduct or carry on any shooting gallery or room where rifle or pistol shooting is practiced, in the City of Indianapolis, without first having procured a license so to do, as hereinafter provided
Keywords: SHOOTING RANGES OR GALLERIES